Philosophers in conversation : interviews from the Harvard review of philosophy - Harlan, Joshua; Upham, S. Phineas (Routledge, 2002)
This volume brings together 13 interviews with some of the brightest names in contemporary philosophy, including W.V.O. Quine, Richard Rorty, Stanley Cavell, Hilary Putnam, as well as John Rawls. Covering a wide range of topics from the philosophy of law and logic to metaphysics to literature, the interviews in this text provide an introduction to some of the most influential thinkers of the day.